Violence sexuelles en milieu universitaire: Synthèse des résultats de l’enquête ESSIMU au Québec - Bergeron, Manon; Hébert, Martine; Ricci, Sandrine; Goyer, Marie-France; Duhamel, Nathalie; Kurtzman, Lyne; Rousseau, Catherine; Auclair, Isabelle; Clennett-Sirois, Laurence; Daigneault, Isabelle; Damant, Dominique; Demers, Stéphanie; et al. (Canadian Woman Studies/les cahiers de la femme, 2018)
This study, “Enquête Sexualité, Sécurité et Interactions en Milieu Universitaire,” conducted in 2016 with 9,284 respondents from six francophone Quebec universities, provided a portrait of sexual violence taking place in a university context. This article presents a summary of the results extracted from the research report (Bergeron et al., 2016).